A Possible Slavic Etymology of Hungarian kullancs ’tick’ - Galac, Ádám (Slavica, 2018)
The present article is dedicated to the etymology of the Hungarian noun kullancs ”клещ (lat. Ixodes ricinus)”. The Slavic origin of the word was assumed in the 19th century, however this idea was rejected in the 20th century owing to phonetic reseasons. After a short overview of the history of the research of this word, arguments are lined up in favour of the fact that the phonetic difficulties can be ignored or at least taken as irrelevant when comparing the Hungarian word kullancs with its Slavic equivalents. Therefore, it is inevitable to raise the question of its Slavic origin again.